Differential Diagnosis for Pericoronal Radiolucencies affecting Jaws – A Case Report on Dentigerous Cyst - Mohana Bhoraskar; Ceena Denny E; R. Arvind; Ravikiran Ongole; Almas Binnal; Nidhi Manaktala (Institute of Medico-legal Publications Pvt Ltd, 2021)
Most of the times it is difficult for the clinicians to confirm the clinical diagnosis without investigationsas the clinical picture of oral lesions may be similar to many other conditions. Hence, appropriate clinicalexamination, coupled with radiological and histopathological investigations could aid in appropriatediagnosis and management of the lesions. This article elaborates on differential diagnosis for pericoronalradiolucencies affecting the jaws in a patient presented for a routine dental examination. Differentialdiagnosis helps us to diagnose a specific lesion by eliminating those lesions which appear clinically similar.As advanced diagnostic aids are available, decision-making has become much easier for these lesions.